KOMUNIKASI ANTARPRIBADI MELALUI MEDIA SOSIAL (SKYPE) PADA MAHASISWA UNIVERSITAS RIAU - Desi Maria Manalu; Evawani Elsya Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Social media presence today makes communication more easily done anytime, anywhere, and anyone. Skype is a social media that has video call feature that can communicate while looking at the other person despite the long distances. The purpose of this research is to find out the process interpersonal communication through social media (Skype) on college students in Riau University.This research used qualitative methods descriptive which the data was obtained through interviews, documentation, and reference materials. As well as using CMC (Computer Mediated Communication) as interaction between people using networked computers with internet. This research presented the subject are students from various faculties at the Riau University. Data analysis technique used in this research is an interactive analysis model and data validity checking technique used is an extension of participation and triangulation.The results showed that Skype gives ease of communication for students Riau University who have interpersonal long distance relationship. Skype has created many new possibilities that sometimes clouds according to the previously difficult or even never imagined could be done.This social networking site allows users to interact without distance limitations, place and time.Keywords : social media, Skype, interpersonal communication, CMC